Examining evidence for behavioural mimicry of parental eating by adolescent females: an observational study - Sharpes, Maxine; Higgs, Suzanne; Blissett, Jacqueline; Nouwen, Arie; Chechlacz, Magdalena; Allen, Harriet A.; Robinson, Eric (Elsevier, 2015)
Behavioural mimicry is a potential mechanism explaining why adolescents appear to be influenced by their parents’ eating behaviour. In the current study we examined whether there is evidence that adolescent females mimic their parents when eating. Videos of thirty-eight parent and female adolescent dyads eating a lunchtime meal together were examined. We tested whether a parent placing a food item into their mouth was associated with an increased likelihood that their adolescent child would place any food item (non-specific mimicry) or the same item (specific mimicry) in their mouth at three different time frames, namely during the same second or within the next fifteen seconds (+15), five seconds (+5) or two second (+2) period. Parents and adolescents’ overall food intake was positively correlated, whereby a parent eating a larger amount of food was associated with the adolescent eating a larger meal. Across all of the three time frames adolescents were more likely to place a food item in their mouth if their parent had recently placed that same food item in their mouth (specific food item mimicry), however there was no evidence of non-specific mimicry. This observational study suggests that when eating in a social context there is evidence that adolescent females may mimic their parental eating behaviour, selecting and eating more of a food item if their parent has just started to eat that food.